Kissing nevus of the penis. Report of two cases and review of the literature - Songting Wang; Mingshu Zhou; Jianjun Qiao (Anais Brasileiros de Dermatologia, 2014)
Kissing nevus is a curious type of nevus that was first described on the eyelids and rarely described on the penis. We report two cases of kissing nevus of the penis and review previously reported cases. The lesions of the kissing nevus of the penis showed characteristic mirror-image symmetry relative to the coronal sulcus. On histopathology, the lesion showed a compound nevus.